2014
DOI: 10.5455/2320-6012.ijrms20140529
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of sella turcica in North Indian population: a radiological study

Abstract: Background: The purpose of this study was to describe the morphology and measure the size of the sella turcica in North Indian population. Methods: Lateral cephalometric radiographs of 180 individuals (90 males and 90 females) with an age range of 12-65 years were taken. Morphology of sella turcica was studied and various measurements were taken to determine the shape of the sella. Statistical analysis was done to calculate differences in dimensions and to establish if any, relationship exists between age, sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 24 publications
3
25
3
Order By: Relevance
“…[4,19] We, therefore, believe that our CT study provides more accurate results than other studies that typically use cephalometric radiography.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…[4,19] We, therefore, believe that our CT study provides more accurate results than other studies that typically use cephalometric radiography.…”
Section: Discussionmentioning
confidence: 75%
“…In the study by Najim and Al-Nakib, [13] a statistically significant difference was noted only in sella depth. Chauhan et al [4] reported that sella dimensions were larger in the higher age group compared to the lower age group. Similarly, Preston [18] determined a close correlation between sella area and age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the studying population, the prevalence of irregularity on the posterior part of the dorsum sellae was reported as 15%, and the bridging of sella turcica was reported as 8%. Unlike the others, Chauhan et al (2014) [13] noted that only 28% of the cases observed had anatomical variations. Anatomical variations included an oblique anterior wall (23%), irregular sella (18%), bridging (17%), and double contour floor (10%).…”
Section: Discussionmentioning
confidence: 99%